A World War I timeline - Dell, Pamela (North Mankato, Minnesota Capstone Press, 2014)
"In timeline format, covers the chronology of major events of World War I"-
A gift from book Africa
History
1 2 13 15
NEW_ZTN_GN
Keywords: JUVENILE NONFICTION -- History -- Military & Wars; World War, 1914-1918 -- Chronology -- Juvenile literature